Effect of moon light and lunar periodicity on the attraction of black cutworm Moth Agrotis Flammatara (Schiffer - Mueller) on light trap - P. N., Mishra; M. P., Singh; M. C., Nautiyal (Universiti Putra Malaysia Press, 1999)
The effect of moon light and lunar periodicty on the attraction of cutworm moth, Agrotis flammatra (Schiffer Mueller) was studied during active periods (rainy season) in 1997 and 1998 at Horticulture Research Block of Hill Campus, Ranichauri (1600m ASL). In the light trap, a mercury vapour electric bulb (160 Watt) was used as the source of light. The moths attracted to the light trap during the active period were collected and recorded daily. Number of moths trapped on the light trap was correlated with the degree of moon phase of different days of a lunar cycle. The results indicated that the number of moths attracted to light trap was consistently very low during moonlight nights around full moon. A highly significant inverse linear correlation between the degree of moon phase and light trap catches was observed. On the average, the attraction response of cutworm moths was stronger in descending phase as compared to ascending phase.